Implementasi Undang-Undang Keterbukaan Informasi Publik di Pemerintah Kabupaten Pesawaran - , IHSAN TAUFIQ ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This thesis is the result of qualitative research that describes the implementation of Law No. 14 of 2008 on Public Information (Freedom of Information Law) in Pesawaran District. Pesawaran District Government has been doing the collection of data and information though not sorted by category information mentioned in the Freedom of Information Law. Delivery of information to the public activities delivered through the public media and publishing media itself in the form of magazines and websites. Unfortunately, the substance of the information submitted is limited to the implementation of routine activities and the achievement of development, has not been touched on other information according to the Freedom of Information Law must complete communicated to the public. PPID role as implementers of Freedom of Information Law is not optimal. Various activities that substantially supports implementation of disclosure has not been well coordinated so impressed walk on their own that can not be maximized as an instrument that can fulfill the mandate of the Freedom of Information Law. Weak knowledge and commitment PPID be factors intertwined with the working poor management of PPID. There needs to be a breakthrough in order to build a better and PPID can carry out the mandate of the Freedom of Information Law optimally amid a variety of limited means, budget and facilities are perceived in Pesawaran District. Keywords: Freedom of Information Law, PPID, information management, information delivery, implementation constraints